2020
DOI: 10.1371/journal.pone.0218494
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium dobesilate reduces VEGF signaling by interfering with heparan sulfate binding site and protects from vascular complications in diabetic mice

Abstract: Inhibiting vascular endothelial growth factor (VEGF) is a therapeutic option in diabetic microangiopathy. However, VEGF is needed at physiological concentrations to maintain glomerular integrity; complete VEGF blockade has deleterious effects on glomerular structure and function. Anti-VEGF therapy in diabetes raises the challenge of reducing VEGF-induced pathology without accelerating endothelial cell injury. Heparan sulfate (HS) act as a coreceptor for VEGF. Calcium dobesilate (CaD) is a small molecule with v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…However, its mechanism(s) in mediating these events has remained unknown. Consequently, we hypothesized that CaD might reduce monocyte-to-macrophage differentiation, one specific hallmark of inflammation (and atherosclerosis) that involves signaling via PKCδ and MAPK, previously shown as mediators of CaD activity in a diabetes model [ 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, its mechanism(s) in mediating these events has remained unknown. Consequently, we hypothesized that CaD might reduce monocyte-to-macrophage differentiation, one specific hallmark of inflammation (and atherosclerosis) that involves signaling via PKCδ and MAPK, previously shown as mediators of CaD activity in a diabetes model [ 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD14 and TLR4 play a vital role in initiating sterile inflammation related to atherosclerosis [ 2 , 3 , 28 ]. Therefore, the effect of CaD to decrease CD14 and TLR4 expression could offer one mechanism to explain why CaD inhibits NF-κB and suppresses the release of downstream NF-κB activation products—TNFα, IL-1β, IL-6, and MCP-1 in animal models of sepsis and diabetic nephropathy and retinopathy [ 11 , 13 , 14 , 32 ]. Indeed, in this study, CaD demonstrated potent anti-inflammatory effects by suppressing TNFα, IL-1β, and MCP-1 levels in PMA, LPS, and high glucose-treated THP-1 cells, which CaD significantly suppressed, suggesting a broad therapeutic spectrum potential of CaD [ 11 , 12 , 13 , 14 , 32 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CaD binds to the heparin-binding domain of FGF-1, thus reducing FGF-1 activity. CaD could act as a new VEGF antagonist without adverse side effects [3].…”
Section: Introductionmentioning
confidence: 99%